2021
DOI: 10.3390/cells10020215
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Aquaporins in Novel Therapies for Male and Female Breast and Reproductive Cancers

Abstract: Aquaporins are membrane channels in the broad family of major intrinsic proteins (MIPs), with 13 classes showing tissue-specific distributions in humans. As key physiological modulators of water and solute homeostasis, mutations, and dysfunctions involving aquaporins have been associated with pathologies in all major organs. Increases in aquaporin expression are associated with greater severity of many cancers, particularly in augmenting motility and invasiveness for example in colon cancers and glioblastoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 185 publications
0
18
0
Order By: Relevance
“…Delicate regulation of intracellular levels of H 2 O 2 opens possibilities in the stimulation of proliferation and survival mechanism for tumour cells, leading to resistance and increased mobility. Aquaporins were found to be upregulated in numerous tumours [ 28 , 75 , 76 ] opening possibilities to target them as a part of tumour therapy. The exact mechanisms and signalling pathways affected by aquaporins are still to be determined, but it is not a simple and straightforward interaction.…”
Section: Aquaporins Oxidative Stress and Cancermentioning
confidence: 99%
“…Delicate regulation of intracellular levels of H 2 O 2 opens possibilities in the stimulation of proliferation and survival mechanism for tumour cells, leading to resistance and increased mobility. Aquaporins were found to be upregulated in numerous tumours [ 28 , 75 , 76 ] opening possibilities to target them as a part of tumour therapy. The exact mechanisms and signalling pathways affected by aquaporins are still to be determined, but it is not a simple and straightforward interaction.…”
Section: Aquaporins Oxidative Stress and Cancermentioning
confidence: 99%
“…In breast cancer, AQP expression is significantly associated with overall survival and relapse free survival (18,19). AQPs impact tumor growth and metastasis by regulating proliferation, migration, and angiogenesis in mammary tumors and breast cancer cell lines (12,(19)(20)(21). Although we are beginning to understand the importance of AQPs in cancer, further elucidation of AQP structure and function will shed light into the additional and unexpected roles of these transport proteins and how their dysregulation can lead to disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, additional research, particularly in the third millennium, for instance a study by Ala [ 106 ], has revealed that their cooperation in water transmission control can be manipulated to address other burden-imposing diseases, including cirrhosis, heart failure, Meniere’s disease, cancer, bullous pemphigoid, eczema, and Sjogren’s syndrome. Khan [ 103 ] shows the important association between breast cancer and aquaporins, underlining that AQPs 1, 3, and 5 are highly expressed in breast, endometrial, and ovarian cancers, consistent with their gene regulation by estrogen response elements. Bystrup [ 107 ] considers that understanding the underlying molecular mechanisms of how AQP5 contributes to cancer development and progression is crucial for the potential use of AQP5 as a prognostic biomarker and for the development of targeted intervention strategies for the treatment of breast cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…Future Trends and Potential Therapeutic Targets in Breast Cancer 3.6.1. Aquaporins Aquaporins (AQPs) are membrane channels that belong to the large family of major intrinsic proteins (MIPs), of which there are thirteen classes with tissue-specific distributions in humans, as summed up by Khan [103] and Magouliotis [104]. As important physiological modulators of water and solute homeostasis, mutations and dysfunctions in aquaporins have been linked to pathologies in all major organs.…”
Section: Prognosismentioning
confidence: 99%